Multidrug resistant tuberculosis in a Marginal Urban Hospital in Lima 2006-2008 - Crispín P., Víctor (2011)
Tuberculosis is a public health problem in the world and Peru, aggravated by multidrug (MDR-TB) and extensively resistant (XDR-TB) forms. The objetives were to describe the resistance to tuberculosis drugs and risk factors to acquire MDR-TB in a marginal urban hospital of Lima, since 2006 to 2008. It is a reported cases studyand was undertaken in Huaycán Hospital. The data collected were acquired from the routine reports of the National Control Program and clinical history. A total of 61 cases of MDR-TB, one of XDR-TB and 7 cases of mono resistant tuberculosis were evaluated; 38 were men (55%) and 31 women (45%). The more affected age group were 15 to 34 years with 55 cases (79,6%). The more frecuent risk factors founded to acquire MDR-TB were: suspicion of failure (FS1, 34 cases, 49%) and failure of treatment one scheme (F1, 14 cases, 20%), and to have had contact with MDR-TB patients (MDR-TB-C, 12 cases, 17%). 76% of cases were resistant from 2 to 5 drugs and 13% from 6 to 9 drugs. There were 32 different resistant patterns to drugs. All cases were treated with individualizad schemes, in 41 cases the treatment was successful (59.4%), 16 cases abandoned the treatment (23,2%) and 6 died (8,7%). In conclusion MDR-TB affect young people, the suspicion of failure and failure of treatment and have been in contact with MDR-TB patiens, were the more frecuent risk factors.